Fragmentation, Globalization and Labor Markets - Michael Burda; Barbara Dluhosch (Center for Economic Studies and ifo Institute (CESifo), 2000)
Fragmentation of the value-added-chain is modeled as the reaction of monopolistically competitive firms to the removal of barriers to trade and factor mobility in an integrated trading environment. Since fragmentation requires high-skilled labor, this form of globalization can induce labor market effects similar to those caused by skill-biased technical change. In the short run, it is likely that fragmentation will be accompanied by an increase in high and low-skilled service employment as well as in the skilled wage premia, as observed in OECD countries. These implications can be reversed, however, as new firms enter the market.
Keywords: 330; International trade; organization of production; technology choice; division of labor